Photocatalytic Activation of Saturated C–H Bond Over the CdS Mixed-Phase Under Visible Light Irradiation - She, Houde; Li, Liangshan; Zhou, Hua; Wang, Lei; Huang, Jingwei; Wang, Qizhao (Frontiers in Chemistry, 2018)
Selective activation of saturated C–H bond in hydrocarbons to produce high-value-added chemicals is of great significance for chemical synthesis and transformation. Herein, we present a facile procedure to achieve Ni-doped CdS nanoparticles with mixed (cubic and hexagonal) phases, as well as its application to the photocatalytic activation of saturated primary C–H bond of toluene and its derivatives. The photocatalytic oxidation rate of toluene into benzaldehyde of formation reached up to 216.7 μmolh-1g-1 under visible light irradiation. The excellent photocatalytic performance of Ni(II)-doped CdS (Ni(II)/CdS) can be attributed to its unique structural assembly with cubic and hexagonal phases and also the addition of Ni ions, together taking effect in promoting the separation of photogenerated charge carriers. The possible reaction mechanism for the photocatalytic selective oxidation is illustrated in this work. The band width of the as-prepared mixed phase CdS is reduced, which can effectively expand the response range and improve photocatalytic performance.